O ACESSO AOS BENEFÍCIOS EVENTUAIS NO CRAS CRISTO REDENTOR - SANTOS, PAULA MARIA DE MOURA (2020)
This study analyzes the eventual benefits of the National Social Assistance Policy, based on the reality of its provision in the municipality of João Pessoa, and uses the situation of these benefits in CRAS Cristo Redentor as an empirical object. With regard to specific objectives, we sought to examine the legal frameworks, jointly defined, referring to eventual benefits, as well as investigating the normative configuration of these eventual provisions assumed in the city of João Pessoa. The exploratory methodological path was theoretically guided by the historical-dialectical method for apprehending reality, using bibliographic and documentary research to systematically survey information. The results show that the strict criteria, the lack of transparency and excessive bureaucratization, in addition to the small budget, drastically limit the attendance to dramatic food needs, much more pertinent with the food security policy, making access to eventual benefits a painful exercise and uncertain for the user.